2011
DOI: 10.1177/1087724x10383583
|View full text |Cite
|
Sign up to set email alerts
|

NCDOT Quality Control Methods for Weigh-in-Motion Data

Abstract: At hundreds of weigh-in-motion (WIM) stations, state departments of transportation (DOTs) collect WIM data 24/7 to meet federal traffic reporting requirements. The North Carolina Department of Transportation (NCDOT) collects WIM data using procedures consistent with recommended industry practices to estimate static vehicle axle weights based on dynamic traffic measurements. Data errors and poor quality data are captured regardless of the technology used, and a quality control (QC) process is an important part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…North Carolina DOT provided 12 consecutive months of calibrated volume and weight data for each WIM station. A quality control procedure confirmed that the data were reliable (16).…”
Section: Traffic Datamentioning
confidence: 79%
“…North Carolina DOT provided 12 consecutive months of calibrated volume and weight data for each WIM station. A quality control procedure confirmed that the data were reliable (16).…”
Section: Traffic Datamentioning
confidence: 79%
“…The quality control procedure confirmed that the data were reliable. For the worst cases only 5% of the data were excluded (12).…”
Section: Traffic Datamentioning
confidence: 99%
“…Accurate records in WIM data are essential to the success of pavement design related to long-term pavement performance and load-pavement impact (2,3). Much research has been conducted with respect to quality assurance (4) and quality control procedures (5)(6)(7) addressing the accuracy performance of various traffic patterns recorded from WIM equipment. However, little work has been done in the field of classifying vehicles that WIM systems failed to classify.…”
mentioning
confidence: 99%